2021
DOI: 10.31234/osf.io/8mbsk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An academic survey on theoretical foundations, common assumptions and the current state of consciousness science

Abstract: We report the results of an academic survey into the theoretical and methodological foundations, common assumptions and the current state of the field of consciousness science. The survey consisted of 22 questions, was distributed online and at two different occasions of the annual meeting of the Association of the Scientific Study of Consciousness (ASSC, 2018 and 2019), targeting active scientists in the field only. We examined responses from 232 consciousness scientists with different backgrounds (e.g., phil… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…sentience) will be created, or are at least theoretically possible (see, for example, Thompson, 1965;Aleksander, 1996;Buttazzo, 2001;Blackmore, 1999;Franklin, 2003;Harnad, 2003;Holland, 2007;Chrisley, 2008;Seth, 2009;Haikonen, 2012;Bringsjord et al, 2015;Reese, 2018;Anthis and Paez, 2021;Angel, 2019). Surveys of cognitive scientists (Francken et al, 2021) and artificial intelligence researchers (McDermott, 2007) suggest that many are open to this possibility. Tomasik (2011), Bostrom (2014), Gloor (2016a), and Sotala and Gloor (2017) argue that the insufficient moral consideration of sentient artificial entities, such as the subroutines or simulations run by a future superintelligent AI, could lead to astronomical amounts of suffering.…”
Section: Introductionmentioning
confidence: 99%
“…sentience) will be created, or are at least theoretically possible (see, for example, Thompson, 1965;Aleksander, 1996;Buttazzo, 2001;Blackmore, 1999;Franklin, 2003;Harnad, 2003;Holland, 2007;Chrisley, 2008;Seth, 2009;Haikonen, 2012;Bringsjord et al, 2015;Reese, 2018;Anthis and Paez, 2021;Angel, 2019). Surveys of cognitive scientists (Francken et al, 2021) and artificial intelligence researchers (McDermott, 2007) suggest that many are open to this possibility. Tomasik (2011), Bostrom (2014), Gloor (2016a), and Sotala and Gloor (2017) argue that the insufficient moral consideration of sentient artificial entities, such as the subroutines or simulations run by a future superintelligent AI, could lead to astronomical amounts of suffering.…”
Section: Introductionmentioning
confidence: 99%
“…It is largely accepted that consciousness is a gradual phenomenon ( Francken et al, 2021 ). It was also suggested that even a single cell may have a minimum level of consciousness, based on the complexity of behavior and complexity of information-processing within each cell ( Reber, 2016 ; Baluška and Reber, 2019 ).…”
Section: Hypothesis and Theorymentioning
confidence: 99%
“…However, the path toward a solution can be achieved by other mechanisms. The free energy principle [the basis of Predictive Processing Theory (PPT), e.g., Hohwy and Seth, 2020 ; Francken et al, 2021 ] predicts that all sentient beings minimize uncertainty for energetic reasons ( Friston, 2003 ). According to PPT, all interaction with the environment involves constant amendment between perceptual input and the internal models ( Friston et al, 2016a ).…”
Section: Our Current Understanding Of Insightmentioning
confidence: 99%